Analisis Pemangku Kepentingan dalam Pengembangan Energi Terbarukan: Studi Kasus Pembangkit Listrik Tenaga Surya (PLTS) Desa Muara Enggelam - Adhityo Nugraha Barsei; Joko Saptohadi (Inovasi, 2023)
Muara Enggelam Village is located in Kutai Kartanegara Regency, East Kalimantan Province. Limited access to electricity makes it difficult for rural communities to carry out their economic activities. The abundant potential of solar resources has encouraged the Kutai Kartanegara Regency Government through the Ministry of Energy and Mineral Resources (ESDM) to develop Renewable Energy (EBT). With these efforts, Muara Enggelam Village can benefit from low-cost electricity from a solar power plant (PLTS) who managed by BUMDes "Bersinar Desaku". Until now, the community has been able to maximize its activities in the fisheries, agriculture, and cottage industries. The sustainable development of PLTS cannot be realized in a short time, there are many stakeholders who contributed to Muara Enggelam Village’s PLTS. Research about stakeholder analysis in renewable energy has never been done before. This study aims to analyze: (1) Who are the stakeholders involved in PLTS in Muara Enggelam Village; (2) What is the strategic role of these stakeholders, and (3) What are the factors that support and hinder the management of PLTS in Muara Enggelam Village. This research is descriptive qualitative research by conducting bold in-depth interviews, documentation, and literature study. The data analysis technique uses the ATLAS.ti application based on the theory regarding the role of stakeholders. The results of this study are that there are 15 stakeholders involved directly or indirectly, the central government, local governments, village governments, academics, BUMDes, the private sector, and community groups. This research can be used as input and strategy for local governments as a sustainable NRE strategy development.